Effects of chloride attack on concrete with the replacement of natural sand by manufactured sand as fine aggregate - Shanmugavadivu, P.M.; Malathy, R. (Journal of Structural Engineering, 2024)
Concrete is a mixture of cement, fine aggregate, coarse aggregate and water. Natural river sand is the most commonly used material as fine aggregate in concrete. Nowadays there is a lot of demand for the natural sand for ever growing construction activities, but natural river sand has becoming rare due to over sand mining and various regulations in different countries in order to protect the environment. So it’s the time to find out a new alternative material for replacing the sand. Many research activities are going on the replacement of fine aggregate by various industrial wastes like fly ash, pond ash, recycled aggregate, crushed glass, quarry waste, etc., In this paper one of such waste material, a residue, tailing or other non-valuable material obtain from quarries after the extraction and processing of rocks, which is known as manufactured sand is used as fine aggregate in concrete. The specific gravity and the gradation of both natural sand and manufactured sand are experimentally determined. Mix proportions for M 20 grade concrete as per IS: 10262, 1982 is arrived based on these values. The effects of chloride attack on concrete with manufactured sand and also with natural sand are determined by performing various tests such as Chloride attack, Corrosion test and Rapid chloride penetration test. The suitability of manufactured sand as fine aggregate for concrete has been assessed by comparing the results with that of conventional concrete. The manufactured sand has performed better than the conventional sand concrete.